miR-34a and miR-21 as biomarkers in evaluating the response of chemo-radiotherapy in Egyptian breast cancer patients - Shaban, Nadia Z.; Ibrahim, Nashwa K.; Saada, Helen N.; El-Rashidy, Fatma H.; Shaaban, HebatAllah M.; Farrag, Mostafa A.; ElDebaiky, Khaled; Kodous, Ahmad S. (Journal of Radiation Research and Applied Sciences, 2022)
MiRNA-21 (miR-21) promotes the initiation and progression of tumor by initiating cell cycle differentiation, while miR-34a induces apoptosis through activating the tumor-suppressor gene p53, and by repressing the anti-apoptotic protein, B-cell lymphoma 2 (Bcl2). To investigate if the expression folds change of circulating miR-21 and miR-34a could be a potential marker to evaluate the response of female breast cancer (BC) patients to the chemo-radiotherapy treatment. and Methods: The study included 159 BC patients and 58 healthy females. Among patients’ 56 were Luminal A, 41 Luminal B, 15 Her-2/neu and 47 Basal like. Regarding stages, 118 BC patient were stage II, 12 stage I, and 29 stage III. Data of miR-21 and miR-34a were correlated with Bcl2, the breast cancer susceptibility genes BRCA1, and BRCA2, and p53. The expression of miR-21 is upregulated (p < 0.001) in BC patients while miR-34a, is downregulated (p < 0.001), compared to control. The application of chemo-radiotherapy treatment decreased (p < 0.001) miR-21 and increased (p < 0.001) miR-34a. MiR-21 directly correlates with Bcl2 (p < 0.001) while miR-34a directly correlates with BRAC1, BRAC2 and p53 (p < 0.001). Conclusion: miR-34a and miR-21 may be considered as promising non-invasive biomarkers in evaluating the response of BC female patients to chemo-radiotherapy. •Dysregulation of miRNAs expression is implicated in the diagnosis of breast cancer (BC).•miR-21 and miR-34a correlate with Bcl2, BRCA1, BRCA2, and p53 in BC.•miR-21 and miR-34a can predict the response of breast-cancer patients to chemo-radiotherapy.